The deep & dark blue - Smith, Niki (Little, Brown and Company, 2020)
A political coup forces twins Hawke and Grayson to escape and assume new identities. They meet the Communion of Blue--an order of women who can manipulate reality. As they begin to understand the magic of the Communion, they hatch a plan to avenge their family and retake their kingdom. Hawke looks to regain his former life, but Grayson realizes she can have a new life that will allow her to live as a girl.